Ultra-Barcoding Discovers a Cryptic Species in Paris yunnanensis (Melanthiaceae), a Medicinally Important Plant - Ji, Yunheng; Liu, Changkun; Yang, Jin; Jin, Lei; Yang, Zhenyan; Yang, Jun-Bo (Frontiers in Plant Science, 2020)
Ultra-barcoding is a technique using whole plastomes and nuclear ribosomal DNA (nrDNA) sequences for plant species identification. Paris yunnanensis is a medicinal plant of great economic importance for the pharmaceutical industry. However, the alpha taxonomy of P. yunnanensis is still uncertain, hindering effective conservation and management of the germplasm. To resolve long-standing taxonomic disputes regarding this species, we newly generated the complete plastomes and nrDNA sequences from 22 P. yunnanensis accessions. Ultra-barcoding analyses suggest that P. yunnanensis as currently circumscribed is made up of two distinct genetic lineages, corresponding to the two phenotypes (“typical” and “high stem” form) identified early in our study. With distinct morphologies and distribution, the “high stem” form should be recognized as a previously unrecognized species; here it is described as a new species, P. liiana sp. nov. Moreover, the ultra-barcoding data do not support treatment of P. yunnanensis as a conspecific variety under Paris polyphylla. Our study represents a guiding practical application of ultra-barcoding for discovery of cryptic species in taxonomically challenging plant taxa. The findings highlight the great potential of ultra-barcoding as an effective tool for resolving perplexing problems in plant taxonomy.